ANALISIS SEKTOR EKONOMI UNGGULAN KABUPATEN BENGKALIS DENGAN PENDEKATAN SEKTOR PEMBENTUKAN PRODUK DOMESTIK REGIONAL BRUTO - Novita, Yola; ', Rosnita; ', Eliza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The growth of an area was determined by GDP potency in that area. So the area government can made the priority of growth plan to leading sector and not leading sector. This research was aims to analyze GDP sector growth profile, basic sector, and competitiveness potency sector. The data used GDP year 2008-2009 with oil and gas and non oil and gas. The tool analysis used Location Quotient (LQ) analysis and for analysis growth and competitiveness potency sector used Shift Share analysis. GDP growth profile without oil and gas, the sector included quadrant 1 (fast growth) that was processing industry sector, electricity and clean water sector, transportation and communication sector, and services sector. GDP growth profile without oil and gas, sector who included quadrant 1 (fast growth) that was transportation and communication sector, and services sector. LQ indeks with oil and gas obtained basic sector that was electricity and clean water sector, hotel and restaurant trade, rent money and company servise sector, and services sector. Shift Share analysis showed GDP with oil and gas that was prosessing industry sector, electricity and clean water sector, transportation and communication sector, and services sector. Shift share without oil and gas that was carriage and communication sector and services sector. Keyword: base sector, leading sector, shift share